Porous carbon material and preparation method and application thereof
By hydrotreating and pre-carbonizing the ethylene tar and combining activation treatment, high-purity porous carbon materials are prepared, which solves the problems of low purity and high preparation cost in the prior art, and achieves efficient and stable preparation of porous carbon materials.
Patent Information
- Application Number
- CN202211007821.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-22
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-08-22
AI Technical Summary
In the prior art, the purity of the porous carbon material is not high and contains a large amount of impurities, resulting in poor stability, reduced capacity and short service life of the electric double layer capacitor. At the same time, the existing preparation process is relatively expensive.
By taking the 250°C to 550°C fraction of ethylene tar, hydrotreated, and after removing impurities, partially hydrotreated ethylene tar is pre-carbonized to obtain coke. Then the remaining hydrogenated refined ethylene tar is mixed with coke and activated to obtain a porous carbon material. This method simplifies the process flow and reduces costs.
The preparation of high-purity porous carbon materials is realized, the stability and energy efficiency of the materials are improved, the preparation cost is reduced, and it is suitable for industrial production.
Smart Images

Figure CN117658128B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of carbon materials, and in particular relates to a porous carbon material and a preparation method and application thereof. Background Art
[0002] Electric double layer capacitor (EDLC) is a new type of energy storage device with high power density and excellent cycle stability. Porous carbon is widely used as the electrode material of electric double layer capacitor.
[0003] Double-layer capacitors utilize a double-layer structure consisting of porous carbon electrodes and electrolytes to obtain ultra-large capacitance. In double-layer capacitors, porous carbon materials are used to make electrodes. Supercapacitors store electrical energy by adsorbing ions in the electrolyte solution through porous carbon, and release electrical energy by desorbing ions in the electrolyte solution through porous carbon. Adsorption and desorption are simple physical processes, and theoretically have a nearly infinite charge and discharge life. However, porous carbon materials are often of low purity and contain a large amount of impurities, such as non-metallic elements such as sulfur, nitrogen, and oxygen, and metallic elements such as iron, nickel, and magnesium. These impurities will chemically react with the solvent or solute in the electrolyte solution, resulting in poor device stability and reduced device capacity and service life.
[0004] The raw materials, additives and preparation process conditions of porous carbon have a great influence on the purity of porous carbon. The raw materials for preparing porous carbon are mainly biomass, coal or petroleum processing derivatives. Among them, biomass and coal contain more impurities such as ash, heavy metals, etc., which are difficult to remove; among petroleum processing derivatives, ethylene tar has the advantages of low ash content, low content of metal and non-metallic impurities, but ethylene tar contains more unsaturated olefins, poor thermal stability, and is easily oxidized in the process of preparing porous carbon, introducing new impurities. In the prior art, the light components in ethylene tar are usually removed and then used to prepare porous carbon. For example, patent document CN106672966A discloses a method for preparing porous carbon using ethylene tar, wherein ethylene tar is pretreated, and the light components therein are removed by refluxing with n-heptane, and then the precursor of porous carbon material is obtained after pre-oxidation, and finally the porous carbon material is obtained by carbonization and acid washing using a template method, but the preparation cost of the template method used in this patent is relatively high.
[0005] Therefore, how to prepare high-purity porous carbon materials and reduce costs is a research hotspot for those skilled in the art. Summary of the invention
[0006] In view of the above-mentioned defects, the present invention provides a method for preparing a porous carbon material, which can achieve the preparation of high-purity porous carbon and has the advantages of simple preparation process and low cost.
[0007] The present invention also provides a porous carbon material which is prepared by the above preparation method and has the advantages of high purity, good stability and the like.
[0008] The present invention also provides a double-layer capacitor, which uses the porous carbon material as an electrode and has the advantages of high energy efficiency, good cycle stability, etc.
[0009] The first aspect of the present invention provides a method for preparing a porous carbon material, comprising the following steps: taking a 250°C to 550°C fraction of ethylene tar, hydrogenating the fraction to obtain hydrorefined ethylene tar; pre-carbonizing a portion of the hydrorefined ethylene tar to obtain coke; mixing the remaining hydrorefined ethylene tar and coke to form a mixture, and activating the mixture to obtain a porous carbon material.
[0010] According to one embodiment of the present invention, the pre-carbonization treatment is performed under an inert atmosphere, and the temperature of the pre-carbonization treatment is 300°C to 800°C.
[0011] According to one embodiment of the present invention, the mass ratio of coke to residual hydrotreated ethylene tar is 1:(0.01-0.8).
[0012] According to one embodiment of the present invention, the mixture is activated by using an activator, and the activator includes at least one of an alkaline compound, water vapor, and carbon dioxide.
[0013] According to one embodiment of the present invention, the activation treatment conditions are: temperature 600° C. to 900° C., and time 0.5 h to 3 h.
[0014] According to one embodiment of the present invention, a fraction within a temperature range of 350° C. to 450° C. is taken from the ethylene tar.
[0015] According to one embodiment of the present invention, the mixture is activated to obtain primary porous carbon; and the primary porous carbon is deoxidized and refined to obtain a porous carbon material.
[0016] According to one embodiment of the present invention, the deoxidation refining treatment is carried out under a vacuum reducing atmosphere, and the conditions of the deoxidation refining treatment are: vacuum degree of -0.1MPa to -0.01MPa, temperature of 300°C to 900°C, and time of 0.5h to 3h.
[0017] The second aspect of the present invention provides a porous carbon material prepared by the above-mentioned preparation method.
[0018] A third aspect of the present invention provides a double-layer capacitor, wherein the electrode of the double-layer capacitor comprises the porous carbon material
[0019] The implementation of the present invention has at least the following beneficial effects:
[0020] The preparation method of the porous carbon material provided by the present invention takes the 250°C-550°C fraction of ethylene tar to obtain a fraction containing impurities such as light components and ash removed, and after hydrogenation of the above fraction, unsaturated structures such as sulfur and nitrogen therein are further removed, and a hydrorefined ethylene tar with extremely low impurity content and good stability is obtained, which is not easy to oxidize and deteriorate during subsequent treatment. The present invention uses the coke obtained after pre-carbonization treatment as the main carbon source, and the remaining hydrorefined ethylene tar as a modifier. The modifier can not only shape the mixture, but also fill the gaps between the coke particles to increase the density of the product. In addition, the structure of hydrorefined ethylene tar is similar to that of coke, and the two can be evenly fused in the subsequent calcination, which promotes the stability of the product and does not introduce new impurities. The preparation method of the porous carbon material provided by the present invention also has the advantages of simple preparation method and high utilization rate of ethylene tar raw materials, and can achieve batch preparation and is suitable for industrial production.
[0021] The porous carbon material provided by the present invention is prepared by the above method and has the advantages of high purity and good stability. It can be used in technical fields such as supercapacitors, biomedicine, catalysis, etc., especially as an electrode material in double-layer capacitors, so that the double-layer capacitors have the advantages of high energy efficiency and good cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 is a flow chart of a method for preparing a porous carbon material in one embodiment of the present invention;
[0023] Figure 2 is the charge and discharge curve of the double-layer capacitor of Example 1;
[0024] Figure 3 This is the cycle performance curve of the double-layer capacitor in Example 3. DETAILED DESCRIPTION
[0025] The specific implementations listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementations obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] like Figure 1 As shown, the present invention provides a method for preparing a porous carbon material, comprising the following steps: taking a 250°C-550°C fraction of ethylene tar, hydrogenating the fraction to obtain hydrorefined ethylene tar; pre-carbonizing a portion of the hydrorefined ethylene tar to obtain coke; mixing the remaining hydrorefined ethylene tar and coke to form a mixture, activating the mixture to obtain a porous carbon material.
[0027] According to the method provided by the present invention, a hydrorefined ethylene tar with low impurity content and high carbon content can be obtained by fraction cutting and hydroprocessing, and the tar obtained after pre-carbonization of part of the hydrorefined ethylene tar is used as a carbon source, and the remaining hydrorefined ethylene tar is used as a modifier to prepare a porous carbon material. The method of the present invention can not only realize the deep processing and utilization of ethylene tar, but also improve the purity of the porous carbon material. In addition, the method of the present invention also has the advantages of low cost and simple operation, and can realize batch preparation, which is suitable for industrial production.
[0028] The present invention uses ethylene tar as raw material, which has a wide source and low price. The ethylene tar of the present invention is a product of high temperature condensation in the process of preparing ethylene by cracking method. The source of ethylene tar includes but is not limited to ethylene tar produced by ethylene production device of petroleum refinery, small-scale experimental device for preparing ethylene by cracking, and medium-sized experimental device for preparing ethylene by cracking.
[0029] In some examples of the present invention, the selected ethylene tar can be a mixture of one or more, wherein the mass content of carbon in the ethylene tar is more than 90%, the mass content of sulfur is less than 0.5%, the mass content of nitrogen is less than 0.5%, and the total mass content of metals (iron, aluminum, nickel, copper, etc.) is less than 500 mg / kg. Preferably, the mass content of carbon in the ethylene tar is more than 92%, the mass content of sulfur is less than 0.2%, the mass content of nitrogen is less than 0.2%, and the total mass content of metals (iron, aluminum, nickel, copper, etc.) is less than 100 mg / kg.
[0030] The above-mentioned fraction of ethylene tar can be obtained by conventional fractionation method, and impurities such as light components and ash in ethylene tar can be removed by fractionation. Fractionation includes but is not limited to atmospheric distillation and vacuum distillation. The fractionation process is cut according to the temperature, and the 250℃~550℃ fraction of ethylene tar is cut, and the preferred cutting point is 300℃~500℃, and further 350℃~450℃.
[0031] The present invention further removes unsaturated structures such as sulfur and nitrogen in the ethylene tar fraction by hydrogenating the fraction, thereby obtaining hydrogenated refined ethylene tar with high carbon content and good stability, thereby preventing oxidation and deterioration in subsequent treatment.
[0032] The above-mentioned hydrogenation treatment includes but is not limited to fixed bed hydrogenation and slurry bed hydrogenation, that is, it can be carried out in a fixed bed reactor or in a slurry bed reactor.
[0033] The above-mentioned hydrogenation treatment can adopt conventional hydrogenation conditions in the art, for example, the temperature can be 300℃~450℃, the pressure can be 10MPa~16MPa, the space velocity can be 1h -1 , the hydrogen-oil ratio is 800:1.
[0034] The pre-carbonization treatment of the present invention can be carried out under an inert atmosphere, wherein the inert atmosphere can be at least one of nitrogen, argon, helium and carbon dioxide.
[0035] In some embodiments, the temperature of the pre-carbonization treatment is 300°C to 800°C, preferably 400°C to 550°C.
[0036] The above-mentioned pre-carbonization treatment can be carried out in conventional calcining equipment, and the equipment used includes but is not limited to sintering furnaces such as tubular furnaces and box furnaces or coking devices.
[0037] In order to facilitate the mixing of subsequent reaction raw materials, a pulverization process is usually included after the pre-carbonization process, so that the particle size of the coke is 0.1 micron to 10 mm, preferably 1 micron to 1000 microns, and more preferably 20 microns to 200 microns.
[0038] The above-mentioned pulverizing process can be carried out in conventional pulverizing equipment, including but not limited to at least one of a mechanical pulverizer and a jet pulverizer, preferably a mechanical pulverizer with an anti-metal pollution coating, wherein the anti-metal pollution coating includes ceramic or tungsten carbide.
[0039] In the present invention, the process of mixing the remaining hydrotreated ethylene tar and coke to form a mixture can be carried out under an inert atmosphere. In some embodiments, the mass ratio of coke to the remaining hydrotreated ethylene tar is 1:(0.01-0.8), preferably 1:(0.05-0.2).
[0040] The above-mentioned mixing process includes but is not limited to manual mixing, mechanical mixing, etc., and is preferably performed by introducing an inert gas into a closed mixing container, or by operating in a glove box with an inert atmosphere.
[0041] In the process of forming the mixture, the remaining hydrorefined ethylene tar can be used as a modifier. On the one hand, it can play the role of a binder to form coke, solving the problems of unstable structure and introduction of new impurities of ordinary binders. It can also play the role of a filler to fill the gaps between coke particles and increase the density of the product. On the other hand, the remaining hydrorefined ethylene tar is a precursor of coke, and the two have good compatibility. In the subsequent calcination treatment, the two can be evenly fused, solving the problem of uneven mixing in the traditional method of preparing porous carbon materials, and avoiding the introduction of new impurities, which is conducive to the formation of products with high purity, uniform and stable structure.
[0042] The activation treatment can adopt conventional physical activation method or chemical activation method, or a combination of the two. In some embodiments, an activator is generally used to activate the mixture. Accordingly, the activator includes at least one of alkaline compounds, water vapor, and carbon dioxide. In the specific implementation process of the present invention, an alkaline substance such as potassium hydroxide can be used as an activator, and the remaining hydrorefined ethylene tar, coke, and alkaline substances are mixed to form a mixture, and chemical activation is performed, which is beneficial to increase the specific surface area of the porous carbon material; water vapor or carbon dioxide can also be used as an activator for physical activation, wherein physical activation only needs to control the atmosphere in the furnace to achieve, and no alkaline substance needs to be added during the mixing process. For example, the remaining hydrorefined ethylene tar and coke can be mixed to form a mixture, and the mixture is activated in an atmosphere containing water vapor or carbon dioxide. The specific surface area of the porous carbon material prepared by physical activation is relatively small, therefore, it is preferred to combine physical activation with chemical activation.
[0043] In the specific implementation process of the present invention, the remaining hydrorefined ethylene tar, coke and alkaline compounds are mixed to form a mixture, wherein the alkaline compound includes at least one of potassium hydroxide, sodium hydroxide, sodium carbonate, potassium carbonate, zinc chloride, calcium hydroxide and sodium bicarbonate. The mass ratio of coke to alkaline compound is 1: (0-6), preferably 1: (1-3), and the alkaline compound can be a solid powder, for example, the particle size can be 0.1 micron to 5 mm, preferably 20 microns to 500 microns.
[0044] In the above specific implementation process, an alkaline compound is selected as an activator for activation treatment, and the hydrorefined ethylene tar can also play the role of a coating agent, uniformly coating the surface of the activator to prevent the activator from contacting with water and carbon dioxide in the air during material transfer and causing deactivation, and avoid the escape of alkali metal atoms during the heating process of the activation treatment, which helps to improve the activation efficiency and increase the specific surface area of the porous carbon; in addition, the coating agent effect of the hydrorefined ethylene tar can prevent oxygen in the air from entering the mixture and causing an increase in the oxygen content.
[0045] The porous carbon precursor of the present invention can be in the form of a column or a block. In order to obtain a well-formed product, a forming process is usually included before the activation process, and the forming process can be carried out using conventional equipment, such as an extruder, a tablet press, etc. A certain pressure is applied to the mixture using an extruder or a tablet press to form a column or a block.
[0046] In the present invention, the temperature of the activation treatment is above 600° C., and preferably, the conditions of the activation treatment are: temperature of 600° C. to 900° C., pressure of 0.01 MPa to 0.3 MPa, and time of 0.5 h to 3 h.
[0047] The activation treatment may be performed under an inert atmosphere, wherein the activation atmosphere includes at least one of nitrogen, argon, helium, carbon dioxide, and water vapor.
[0048] The above activation treatment can be carried out in conventional calcination equipment, including but not limited to an atmosphere furnace that meets the above atmosphere environment and has a temperature of 600° C. or above.
[0049] The activation treatment is preferably carried out under a pressure between 0.1 MPa and 0.3 MPa, and can be carried out under normal pressure, for example.
[0050] In the specific implementation process of the present invention, in order to remove excess activator and other impurities, the activated product is usually washed, filtered, dried and ground after the activation treatment. Preferably, it is first washed in an acid solution and then washed in pure water until neutral. The purpose of drying is to remove excess water, and the preferred drying temperature is 100°C to 200°C. The grinding process can be carried out in a mechanical pulverizer, and the particle size after grinding is preferably 2μm-50μm.
[0051] like Figure 1 As shown, in the present invention, in order to further remove the oxygen element and volatile components therein, the mixture is activated to obtain primary porous carbon; and the primary porous carbon is deoxidized and refined to obtain a porous carbon material.
[0052] In the above-mentioned deoxidation refining treatment, the conditions of the deoxidation refining treatment are: vacuum degree of -0.1MPa to -0.01MPa, preferably vacuum degree of -0.1MPa, temperature of 300°C to 900°C, and time of 0.5h to 3h.
[0053] The above deoxidation and refining treatment is carried out under a vacuum reducing atmosphere, and can be carried out in a vacuum operating atmosphere furnace or a vacuum operating reactor. For example, after placing the primary porous carbon in the furnace, the furnace is sealed, and the air in the furnace is first evacuated to a vacuum, and then the connection between the vacuum system and the furnace is cut off, and reducing gas is slowly introduced into the furnace, and the temperature is increased to carry out a reduction reaction, and the supply of reducing gas is maintained until the reaction is completed and cooled to room temperature. After cooling, the product is taken out of the furnace and sealed and packaged to obtain a porous carbon material. Among them, the time for evacuating the furnace can be 120s to 480s.
[0054] In the above deoxidation refining treatment, the reducing gas may be at least one of hydrogen, methane, ethylene and propylene, and the flow rate of the reducing gas is preferably 1 mL / min to 2000 mL / min. The reducing gas is preferably a reducing gas containing 1% to 50% by volume of an inert gas, and the inert gas may be nitrogen, argon or the like.
[0055] The present invention also performs purification treatments such as deoxygenation refining treatment, and adopts a method of first evacuating the air and then filling with reducing gas to perform hydrogenation deoxygenation, which has high deoxygenation efficiency and solves the problem of uneven and incomplete deoxygenation in the ordinary normal pressure displacement method.
[0056] The present invention also provides a porous carbon material, which is prepared by the above preparation method and has the advantages of high purity, uniform and stable structure, etc. It is particularly suitable for the technical fields of supercapacitors, biomedicine, catalysis, etc.
[0057] The above porous carbon material has a specific surface area of up to 500m 2 / g~3500m 2 / g, the total pore volume can reach 0.1cm 3 / g-5cm 3 / g, oxygen content is less than 1wt%, ash content is not higher than 0.1wt%, metal content (iron, nickel, cobalt, copper, aluminum, sodium, potassium) is less than 20mg / kg respectively, and total metal content is less than 50mg / kg.
[0058] The present invention also provides a double-layer capacitor, which uses the above-mentioned porous carbon material as an electrode and has the advantages of high energy efficiency and good cycle stability. Specifically, the first discharge specific capacity of the double-layer capacitor in an organic electrolyte system is not less than 20F / g, or the first discharge specific capacity of the double-layer capacitor in an inorganic electrolyte system is not less than 40F / g.
[0059] In the above-mentioned double-layer capacitor, the electrode material can be prepared by the following method: a porous carbon material, a binder, conductive carbon black, etc. are mixed in a certain proportion to form a slurry, and then the slurry is coated on a substrate to form an electrode.
[0060] The preferred embodiments of the present invention will be described in detail below in conjunction with examples. It should be understood that the following examples are provided only for the purpose of illustration and are not intended to limit the scope of the present invention. Those skilled in the art may make various modifications and substitutions to the present invention without departing from the purpose and spirit of the present invention.
[0061] Unless otherwise specified, the experimental methods used in the examples and comparative examples of the present invention are conventional methods, and the materials, reagents, etc. used in the examples are all commercially available unless otherwise specified.
[0062] Example 1
[0063] The method for preparing the porous carbon material provided in this embodiment comprises the following steps:
[0064] (1) Ethylene tar from Daqing Petrochemical's ethylene plant was selected, and the ethylene tar was fractionated using a real boiling point distillation device to cut the distillate oil in the range of 350°C to 450°C; the distillate oil was hydrogenated using a fixed bed hydrogenation device, and the conditions for the hydrogenation treatment were: reaction temperature 300°C, reaction pressure 10 MPa, and space velocity 1 h -1 , the hydrogen-oil ratio is 800:1, and hydrogenated refined ethylene tar is obtained;
[0065] (2) placing part of the hydrorefined ethylene tar in a kettle coking reactor for pre-carbonization treatment, the atmosphere of the reactor is high-purity nitrogen, the heating rate is 2°C / min, the temperature is raised to 500°C, and the temperature is kept constant for 480min;
[0066] The product at the bottom of the kettle is taken out and crushed in a ball mill. The ball mill and the grinding balls are made of tungsten carbide. The particle size D50 after crushing is in the range of 20-50 μm to obtain coke.
[0067] (3) nitrogen is introduced as a protective gas, and the coke and the remaining hydroprocessed ethylene tar are mixed to obtain a mixture, and potassium hydroxide is used as an activator, wherein the mass ratio of the coke, potassium hydroxide and the remaining hydroprocessed ethylene tar is 1:2.5:0.2, the potassium hydroxide is a powder after pulverization, and the D50 particle size range is 20-50 μm, and the mixing equipment is a rotary mechanical stirrer lined with tetrafluoroethylene material;
[0068] The mixture of the above three was pressed into a cylindrical blank with a diameter of 2 cm and a height of 1 cm under a pressure of 5 MPa using a powder tablet press;
[0069] (4) placing the blank into a corundum crucible with a lid, and placing the crucible in a tube furnace for activation treatment, wherein the activation treatment conditions are: atmosphere of high-purity nitrogen, heating rate of 5°C / min, temperature of 800°C, time of 120min, and pressure of 0.01MPa;
[0070] The calcined product was taken out, poured into a 5% hydrochloric acid solution and stirred for 5 hours, filtered and washed repeatedly with pure water for 3 times, and finally the solid product was collected by filtration and dried at 100°C for 24 hours to obtain a dry product;
[0071] (5) placing the dried product in a quartz crucible, and placing the crucible in a quartz tube vacuum tube furnace for deoxidation and refining treatment, specifically including: extracting the air in the furnace to -0.1 MPa and maintaining the vacuum for 30 minutes, then slowly introducing reducing gas into the furnace (wherein the volume ratio of hydrogen, ethylene and argon is 1:1:8, and the flow rate is 10 mL / min), then turning on the heating, the heating rate is 5°C / min, the temperature is 700°C, and the constant temperature time is 120 minutes; after the reaction is completed, the temperature is naturally lowered to obtain a porous carbon material.
[0072] The double-layer capacitor provided in this embodiment uses the porous carbon material provided in Example 1 as an electrode material, and the assembly of the double-layer capacitor includes the following steps:
[0073] 1) The porous carbon material, the polytetrafluoroethylene binder and the conductive carbon black (JPD600, commercially available) were mixed in a mass ratio of 9:0.5:0.5, and pure water was used as a dispersant, and the mixture was stirred to obtain a slurry;
[0074] 2) The slurry was evenly coated on a nickel foam electrode with a diameter of 13 mm, and then placed in a vacuum oven at 120° C. and dried for 6 h to obtain an electrode;
[0075] 3) Take two electrodes of the same mass, use 6 mol / L potassium hydroxide solution as the electrolyte, use glass fiber filter paper as the diaphragm, use a CR2032 button battery shell as the container, and assemble using a button battery sealing machine to obtain a double-layer capacitor;
[0076] The electrochemical performance of the double-layer capacitor was tested using an electrochemical workstation. The test results are shown in Figure 2 and Figure 3 .
[0077] Example 2
[0078] The method for preparing the porous carbon material provided in this embodiment comprises the following steps:
[0079] Compared with Example 1, in step (3), "using potassium hydroxide as an activator" is replaced by "using water vapor as an activator"; the molding treatment in step (3) is replaced by "extruding the mixture into particles with a diameter of 2-5 mm and a length of 2-5 mm using an extruder to obtain a porous carbon precursor"; the activation treatment condition in step (4) "pressure is 0.01 MPa" is replaced by "pressure is 0.02 MPa", and other conditions remain unchanged.
[0080] Example 3
[0081] The method for preparing the porous carbon material provided in this embodiment comprises the following steps:
[0082] Compared with Example 1, step (1) is replaced by "selecting ethylene tar from the ethylene plant of Fushun Petrochemical Company, using a vacuum distillation device to cut the ethylene tar into fractions, and cutting the distillate oil in the range of 300°C to 350°C; using a slurry bed hydrogenation device to hydrogenate the distillate oil, and the conditions of the hydrogenation treatment are: temperature 450°C, pressure 16MPa, space velocity 1h -1 , hydrogen-to-oil ratio is 800:1, and hydrogenated refined ethylene tar is obtained", and other conditions remain unchanged;
[0083] In the double-layer capacitor provided in this embodiment, the porous carbon material in Example 1 is replaced by the porous carbon material prepared in Example 3, and other conditions remain unchanged.
[0084] Example 4
[0085] The method for preparing the porous carbon material provided in this embodiment comprises the following steps: Compared with Example 1, step (5) is removed, and other conditions remain unchanged.
[0086] Comparative Example 1
[0087] The method for preparing the porous carbon material provided in this embodiment comprises the following steps: compared with Example 1, step (1) is removed, and step (2) is directly implemented with ethylene tar, and the remaining hydrogenated refined ethylene tar is not added to step (3), and step (5) is removed, while other conditions remain unchanged.
[0088] Comparative Example 2
[0089] The method for preparing the porous carbon material provided in this embodiment comprises the following steps: compared with Example 1, the remaining hydrorefined ethylene tar is not added in step (3), and step (5) is removed, while other conditions remain unchanged.
[0090] Comparative Example 3
[0091] The preparation method of the porous carbon material provided in this embodiment includes the following steps: Compared with Example 2, in step (3), the residual hydrorefined ethylene tar is not added, but is replaced by asphalt commonly used in the industry (commercially available, powdered, with a softening point of 250°C) as an additive in an equal mass ratio, and step (5) is removed, that is, no deoxidation refining treatment is performed, and other conditions remain unchanged.
[0092] Table 1 Physical properties of porous carbon materials in Examples and Comparative Examples
[0093]
[0094] According to Table 1, the ash content, metal content and non-metal content of the porous carbon material of Comparative Example 1 are much higher than those of the embodiment, indicating that the impurity content of the product can be greatly reduced after cutting and hydrogenation of ethylene tar. According to Example 1 and Example 4, the oxygen content in the material can be further reduced by performing a deoxidation refining process. Compared with Example 1, in Comparative Example 2, since no hydrorefined ethylene tar was added to coat the activator, alkali metal atoms may have escaped from the activator at high temperature. Under the same ratio of activator to carbon source, the activation efficiency of the activator deteriorated, the specific surface area of the material decreased, and no hydrorefined ethylene tar was added to coat the activator. During the reaction, oxygen will enter the mixture, resulting in an increase in oxygen content, and oxygen cannot be removed without deoxidation. Comparative Example 3, due to the addition of asphalt as a binder, the impurities contained in it are introduced into the product during the preparation process. At the same time, its oxygen content value is relatively high, indicating that the coating effect of asphalt is not as good as that of hydrorefined ethylene tar.
[0095] Figure 2 This is the charge and discharge curve of the double-layer capacitor of Example 1. At a charge and discharge current of 1A / g, the capacity of the capacitor is 238F / g. The charge and discharge curve of the capacitor can maintain a very good symmetrical curve, and the curve does not bend, indicating that the electrode material exhibits a simple double-layer adsorption process during the charge and discharge process, which is a purely physical process. The electrolyte does not react chemically with the electrode material, proving that the content of impurities such as non-carbon elements in the porous carbon material of the present invention is extremely low.
[0096] Figure 3 This is the cycle performance curve of the double-layer capacitor in Example 3. The double-layer capacitor is cycled 20,000 times at a charge and discharge current of 5A / g, and the capacity retention rate of the capacitor is 99%. The adsorption and desorption behavior on the surface of the electrode material is highly reversible, indicating that the porous carbon material of the present invention has a low impurity content, is very stable in properties, and has excellent cyclic performance.
[0097] The method for preparing the porous carbon material provided by the present invention can prepare the porous carbon material with low impurity content and high purity, and can make full use of ethylene tar to reduce the cost of the preparation process.
[0098] The preferred specific embodiments and experimental verification of the present invention are described in detail above. It should be understood that ordinary technicians in this field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in this technical field based on the concept of the present invention through logical analysis, reasoning or limited experiments on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A method for preparing a porous carbon material, characterized in that: The following steps are involved: Taking a 250°C to 550°C fraction of ethylene tar, and subjecting the fraction to hydrogenation treatment to obtain hydrogenated refined ethylene tar; Pre-carbonizing a portion of the hydrorefined ethylene tar to obtain coke; mixing the remaining hydrorefined ethylene tar and the coke to form a mixture, and performing activation treatment on the mixture to obtain the porous carbon material; The mass ratio of the coke to the remaining hydrorefined ethylene tar is 1:(0.01-0.8).
2. The preparation method according to claim 1, characterized in that: The pre-carbonization treatment is carried out in an inert atmosphere at a temperature of 300°C to 800°C.
3. The preparation method according to claim 1 or 2, characterized in that: The mixture is activated by using an activator, wherein the activator comprises at least one of an alkaline compound, water vapor and carbon dioxide.
4. The preparation method according to claim 1 or 2, characterized in that: The activation treatment conditions are: temperature 600° C. to 900° C., time 0.5 h to 3 h.
5. The preparation method according to claim 1 or 2, characterized in that: Take the fraction within the range of 350°C to 450°C of ethylene tar.
6. The preparation method according to claim 1 or 2, characterized in that: The mixture is activated to obtain primary porous carbon; and the primary porous carbon is deoxidized and refined to obtain the porous carbon material.
7. The preparation method according to claim 6, characterized in that: The deoxidation refining treatment is carried out in a vacuum reducing atmosphere, and the conditions of the deoxidation refining treatment are: vacuum degree of -0.1MPa~-0.01MPa, temperature of 300℃~900℃, and time of 0.5h~3h.
8. A porous carbon material, characterized in that: The method is prepared by the preparation method according to any one of claims 1 to 7.
9. An electric double layer capacitor, characterized in that: The electrode of the electric double layer capacitor comprises the porous carbon material according to claim 8.
Citation Information
Patent Citations
Processing method of ethylene cracking equipment byproduct
CN103805271A
Preparation method of ethylene tar-based porous carbon with narrow aperture distribution
CN106672966A